2014
DOI: 10.7314/apjcp.2014.15.13.5377
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quality of Life of Turkish Breast Cancer Patients Receiving Breast Conserving Surgery or Modified Radical Mastectomy

Abstract: Purpose: The aim of this study was to investigate the differences in quality of life in patients who received breast conserving surgery (BCS) or modified radical mastectomy (MRM) for breast cancer. Materials and Methods: A total of 100 women with breast cancer who underwent either BCS or MRM between September 2011 and April 2012 at a private health center and completed their chemotherapy and radiation therapy cycles were included in the study. To assess the quality of life, we used a demographic questionnaire,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
2
11
1
Order By: Relevance
“…Research by other authors later showed similar results [ 29 , 30 ]. In addition, similar findings are found in other papers, namely, women in all ages after radical mastectomy had the worst level of general satisfaction with life [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…Research by other authors later showed similar results [ 29 , 30 ]. In addition, similar findings are found in other papers, namely, women in all ages after radical mastectomy had the worst level of general satisfaction with life [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…Also, studies carried out by Croft et al, (2014) showed that married women who were diagnosed with breast cancer after 5 years from the diagnosis had a higher level of optimism compared to unmarried women. In the studies of Cobo-Cuenca et al, (2018) and Acil and Cavdar (2014) it was shown that women in relationships had greater life satisfaction compared to unmarried women. Demonstrating the relationship between being in a relationship with QOL and women with breast cancer indicates the importance of family support in the fight against the disease.…”
Section: Discussionmentioning
confidence: 98%
“…Breast surgery can be done in two ways, in first one which is called Breast-Conserving Surgery (BCS), only the tumor and some surrounding tissue is removed and natural breast shape is preserved. In the second type called Modified Radical Mastectomy (MRM) the entire breast is removed (Acil et al, 2014). Data analysis was performed using spss version 20 and Cox proportional hazard models was fitted to the data.…”
Section: Methodsmentioning
confidence: 99%